In vitro characterization and molecular epidemiology of Cryptococcus spp. isolates from non-HIV patients in Guangdong, China - Wang, Penglei; Li, Yongming; Gao, Lei; Tang, Xiang; Zheng, Dandian; Wu, Kuihai; Wang, Luxia; Guo, Penghao; Ye, Feng (Frontiers in Microbiology, 2024)
The burden of cryptococcosis in mainland China is enormous. However, the in vitro characterization and molecular epidemiology in Guangdong, a key region with a high incidence of fungal infection in China, are not clear.From January 1, 2010, to March 31, 2019, clinical strains of Cryptococcus were collected from six medical centres in Guangdong. The clinical information and characteristics of the strains were analysed. Furthermore, molecular types were determined.A total of 84 strains were collected, mostly from male and young or middle-aged adult patients. Pulmonary and cerebral infections (82.1%) were most common. All strains were Cryptococcus neoformans, grew well at 37°C and had capsules around their cells.One melanin-and urea-and one melanin+ and urea-variants were found. Although most strains exhibited a low minimum inhibitory concentration (MIC) value for voriconazole (mean: 0.04 µg/mL) and posaconazole (mean: 0.12 µg/mL), the results for these isolates showed a high degree of variation in the MIC values of fluconazole and 5-fluorocytosine, and resistance was observed for 4 out of 6 drugs. A significant proportion of these strains had MIC values near the ECV values, particularly in the case of amphotericin B. The proportion of strains near the clinical breakpoints was as follows: fluconazole: 3.66%; voriconazole: 3.66%; itraconazole: 6.10%; posaconazole: 13.41%; amphotericin B: 84.15%; 5-fluorocytosine: 2.44%. These strains were highly homogeneous and were dominated by the Grubii variant (95.2%), VNI (94.0%), α mating (100%), and ST5 (89.3%) genotypes. Other rare types, including ST4, 31, 278, 7, 57 and 106, were also found.Phenotypically variant and non-wild-type strains were found in Guangdong, and a significant proportion of these strains had MIC values near the ECV values towards the 6 antifungal drugs, and resistance was observed for 4 out of 6 drugs. The molecular type was highly homogeneous but compositionally diverse, with rare types found.Enhanced surveillance of the aetiology and evolution and continuous monitoring of antifungal susceptibility are needed to provide references for decision-making in the health sector and optimization of disease prevention and control.